Controle de motor de indução de média tensão em aplicação de bombeio submarino - Ratzke, Alexandre Salcedo (2017)
This work presents a study of sensorless speed control by field orientation considering the use of a three-phase induction motor fed through long cables through subsea umbilicals. For this study, the adopted electrical model reproduces a system that is used to drive a subsea pump in offshore oil fields. The long tieback and the absence of sensors, as an application requirement, can undermine or compromise motor performance. To make the field-oriented control feasible to the proposed scenario, this work brings the use of field observers and speed estimators instead the use of sensors that are typically used in this type of control. To improve performance, this dissertation brings a technique to compensate the effects of cable and filter installed in the output of the converter. The proposed system is submitted to simulations that reproduce different conditions of predicted field operations. The simulations also show the comparison of the performance of the proposed control against the performance of the system with a scalar control. The results here presented show that the speed control proposed for the application using long cable is robust and feasible.